Experimental Investigation on the Performance of Vegetable Oil Based Cutting Fluids in Drilling AISI 304L Using Taguchi Technique - Jeevan Tamalapura Puttaswamy; Jayaram Saligrama Ramachandra (Tribology Online, 2018)
The demand for renewable and biodegradable cutting fluids is increasing day by day. Owing to the desirable properties of vegetable oils as cutting fluids, an attempt is made to explore the potentiality of plentifully available vegetable oils as a cutting fluid for drilling of AISI 304L stainless steel using Minimum Quantity Lubrication (MQL) method. Taguchi’s orthogonal array (L27) is used for obtaining the experimental design. The performances of two Vegetable oil based cutting fluids (VBCFs) Neem (Azadirachta indica) and Mahua (Madhuca indica) and commercial Mineral oil based cutting fluid (Servocut 945) are compared in terms of thrust force, surface roughness, temperature and tool wear during drilling of AISI 304L stainless steel with carbide tool. Experimental observations and statistical analysis show that Neem and Mahua oils have a considerable potential to be used as an alternative to conventional cutting fluids. Confirmation tests verified that the selected optimal combination through Taguchi design was able to achieve desired performance.